Effects of Excercise on Ghrelin - Algul, Sermin; Ilcin, Saadet; Ozcelik, Oguz (Progress in Nutrition, 2021)
Ghrelin, a gastric derived acylated peptide, was discovered in 1999 as a mediator of growth hormone secretiation. Since then, ghrelin has been found to significant impacts on many physiological functions of body systems. Ghrelin has a potential on appetite stimulation that influence on regulation of energy metabolism. It is known that exercise has a marked impact on energy homeostasis and consequently many research focused on the interaction between exercise stimulus and ghrelin response. This review provides an overwiew of research relating to the acute and chronic effects of exercise on (total, acyl and desacyl) ghrelin levels and also impact of exercise intensity on ghrelin levels. Although there is uncertainty among the results of previous studies, our review suggests that acute exercise transiently enterferes with the acly and total ghrelin levels. However, chronic exercise may acause increase in ghrelin levels in contrast to acute exercise with related to change of body weight. In adition, inenstiy of exercise may also reveales various results concerning the relationship between exercise and circulation ghreline levels. The discovery of ghrelin has raised our knowledge of food intake regulation, energy homeostasis and metabolic function mechanism. Further studies should be focused betwen the impact of exercise (type, duration and intensity) on circulation ghreline levels. Exercise induced ghrelin levels will likely generate new pharmacological approaches to many metabolic diseases based on inbalance in body energy homeostasis.